Empowerment at work: An empirical study on Empowering Leadership and Psychological Empowerment - Serrenho, Rita; dos Santos, Nuno Rebelo; Dionísio, Andreia; da Silva, Paulo Resende (Journal of Positive Management, 2022)
Research Purpose: The aim of the present study is threefold. First, it intends to describe workers’ psychological empowerment in a sample of Portuguese workers. Secondly, to describe empowering leadership perceived by employees about their hierarchical superiors. Finally, to examine the relationships between psychological empowerment dimensions and empowering leadership dimensions. Method: A cross-sectional survey design was adopted with a convenience sample of Portuguese workers (N = 125). Cronbach’s alpha was utilized to examine the reliability of the dimensions. Pearson’s correlation coefficient and simple linear regressions were used to analyze the association between empowering leadership and psychological empowerment dimensions. Measuring Instruments: Spreitzer’s Psychological Instrument and the Empowering Leadership Scale were administered. Main findings: The results revealed significant and positive correlations between empowering leadership and psychological empowerment dimensions, especially employee self-determination. Implications/limitations: This research demonstrates that leaders can have an active role in increasing employee psychological empowerment, which can be an antecedent of positive employee attitudes and work outcomes. It is suggested in future studies to use more extensive and more representative samples. Furthermore, longitudinal and experimental research designs will verify if there is a significant causal relationship between empowering leadership and psychological empowerment. Value of the paper: This study empirically confirms that empowering leadership is associated with employees’ psychological empowerment among Portuguese workers. Keywords: empowering leadership, psychological empowerment, Portuguese workers, Pearson’s correlation coefficient, linear regression Type of paper: Research paper